Secretory IgA, IgG, and IgM Antibodies Contributions in Breast Milk and Risk of Wasting of Babies 7-24 Months - I Made Rai Sudarsono; Imanuddin Imanuddin; Petrus Petrus; Chaerul Saleh (Postgraduate, University of Mataram, 2023)
Wasting is a nutritional problem that can hamper the growth of children under five and affect their future productivity. The prevalence of wasting at Wolo Puskesmas in 2018 was 15.2%, then increased to 26.1% in 2022. Objectives: To determine the risk factors for wasting in under two yearsaged 7-24 months in the Work Area of the UPTD Wolo Health Center, Kolaka Regency.Â This is an observasional analitic research with a case control study design. The population was all under two yearsaged 7-24 months who experienced wasting as many as 25 people and the sample of this study were all under two yearsaged 7-24 months who experienced wasting as many as 25 people and control as many as 25 people. Sampling of cases using total sampling and control using a matching system. Data on exclusive breastfeeding were obtained through interviews and from the KIA book and records at the Health Center, and wasting was obtained from measurements of body weight and height. Data were analyzed using the Odd Ratio (OR) test. Exclusive breastfeeding are risk factors for wasting protection in children aged 7-24 months.This study suggests for mothers who have Baduta to be able to provide nutritious food to protect the IgA, IgG, dan IgM secretoric and regulate Baduta's diet so that it can improve the nutritional status of Baduta and for the Wolo Health Center to routinely provide education about nutrition since pregnant women